Olive mill wastewater as a source of defense-promoting by-products against microbial pathogens - Ascenzo Salvati; Fabio Sciubba; Alessandra Diomaiuti; Gian Paolo Leone; Daniele Pizzichini; Daniela Bellincampi; Daniela Pontiggia (Plant Stress)
Olive oil is a core component of the Mediterranean diet known for its nutritional properties and health benefits. Olive industry is moving to novel extraction systems for higher oil yield and quality and for waste reduction, which is a relevant problem in the process due to its toxicity and high disposal costs. Multi-Phase Decanter (DMF) is a modern two-phase system performed without adding water during the process. Using DMF, a wet by-product indicated as pâté and consisting of the fruit pulp and vegetation water (VW) is recovered. The pâté has a high content of potentially bioactive molecules that may be exploited to promote plant resistance against microbial pathogens. In this work, to identify by/products of biological interest, the VW recovered from the pâté by centrifugation was subjected to fractionation by tangential-flow membrane filtration (TFMF), combining microfiltration (MF) and ultrafiltration (UF). High-resolution NMR spectroscopy indicated the presence of bioactive molecules such as flavonoids, hydroxytyrosol and oleuropein with known antimicrobial activity. High-Performance Anion Exchange Chromatography with Pulsed Amperometric Detection (HPAEC-PAD) was performed to detect the presence of pectic oligosaccharides in the fractions, showing the enrichment, in the UF-concentrate fraction, of oligogalacturonides (OGs), well known for the ability to elicit defense responses and protect plants against pathogen infections. Arabidopsis thaliana plants treated with TFMF fractions displayed induction of defense responses and exhibited tolerance against microbial pathogens without adverse effects on growth and fitness. This study shows that pâté by-products can potentially be exploited in agriculture as sustainable plant phyto-protectant.